Missed Massive Pulmonary Embolism and the Hidden Threat of a Distal Deep Vein Thrombosis - Cynthia Wong BM BS (Journal of Investigative Medicine High Impact Case Reports, 2018)
A 47-year-old woman presented to her GP (general practitioner) surgery with a left leg pain of 4 days duration after a recent 4-hour flight. She was taking the oral combined contraceptive pill and had no past medical history. She had a low predictive Wells score for deep vein thrombosis, but her D-dimer was positive, so she had a proximal lower limb vein ultrasound scan as per the National Institute for Clinical Excellence guidelines, which was negative. Two days later, she presented to the emergency department with a collapse and dyspnea. Her blood pressure was unrecordable in the ambulance, and she was severely peripherally cyanosed with a blood pressure of 64/40 mm Hg in the emergency department. She had a computed tomography pulmonary angiogram, which confirmed extensive bilateral pulmonary emboli with right ventricular strain. She had 2 cardiac arrests while in hospital and is now on long-term anticoagulation.